The Possibilities of Detecting the Manipulation Risk of Information Presented in the Annual Economic Entities’ Financial Statements - Theoretical nd Practical Particularities - Mangu (Giurea), Gabriela; Zuca, Marilena Roxana; Soare, Georgiana - Janina (Acta Universitatis Danubius. Œconomica, 2023)
The creative accounting uses a range of techniques and practices through which the economic entities can change the picture of their financial position and performance. On this regard, items of the balance sheet and income statement are distorted and presented to users of financial and accounting information. The activities of creative accounting on annual accounts involve a series of risks assumed by the management of the entity, and these risks might be diminished by implementing strategies to detect and limit the mechanisms for handling financial and accounting information. Nevertheless, this is difficult to be successful if we take into account the fact that managers largely aim at making use of creative accounting, acting under cover of its legality.